Objectively Measured Physical Activity and Healthcare Expenditures Related to Arterial Hypertension and Diabetes Mellitus in Older Adults: SABE Study - Bueno, Denise Rodrigues [UNESP]; Nunes Marucci, Maria de Fatima; Costa Rosa, Clara Suemi da [UNESP]; Fernandes, Romulo Araujo [UNESP]; Oliveira Duarte, Yeda Aparecida de; Lebao, Maria Lucia (Human Kinetics Publ Inc, 2017)
Research using questionnaires has shown that physical activity level (PAL) is associated with healthcare costs. The purpose of this study was to examine the association between objectively measured PAL and healthcare costs among hypertensive and diabetic noninstitutionalized Brazilian older people. The method consisted of a cross-sectional study forming part of the SABE Study, composed of 377 older people interviewed in 2010. Expenditures were estimated taking into account self-reported medicine prescription, outpatient service, and hospitalizations, with the highest quartile of expenditures considered as a risk category. PAL was estimated using an Actigraph accelerometer. Associations were expressed as odds ratios and 95% confidence intervals, adjusted for covariates. Overall expenditures were higher in the sedentary group. The insufficiently active group presented greater odds for higher total, outpatient, and hospitalization expenditure. It was concluded that healthcare expenditures were lower in more active hypertensive and diabetic older people. The promotion of physical activity could be relevant in the attenuation of the burden of chronic diseases in economic losses.
Keywords: physical activity level; expenditures; older people; accelerometry